2020
DOI: 10.1080/01904167.2020.1730902
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of nutritional diagnostics for phosphorus considering five standards by the method of diagnosing nutritional composition in sugarcane

Abstract: The accuracy of nutritional diagnoses can enable the definition of the best set of standards by the method of nutritional composition diagnosis (CND) in sugarcane. In this sense, the purpose of this study was to perform the accuracy of the nutritional diagnosis for phosphorus and to determine the best set of CND standards in sugarcane. A database of 720 samples was created, using the productivity and foliar concentrations of N,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, phosphorus uptake by plants, in the form of phosphate ions, depends on soil physicochemical parameters ( Pereira et al., 2020 ), the application method and its frequency ( Rady et al., 2018 ; Chtouki et al., 2022 ), the root exudation and architecture ( Khourchi et al., 2022a ), and the rhizosphere microbial activity ( Wahid et al., 2020 ). In this regard, different studies have proven the effectiveness of phosphate solubilizing bacteria (PSB) in improving crop yield due to improved P levels in the soil ( Khourchi et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, phosphorus uptake by plants, in the form of phosphate ions, depends on soil physicochemical parameters ( Pereira et al., 2020 ), the application method and its frequency ( Rady et al., 2018 ; Chtouki et al., 2022 ), the root exudation and architecture ( Khourchi et al., 2022a ), and the rhizosphere microbial activity ( Wahid et al., 2020 ). In this regard, different studies have proven the effectiveness of phosphate solubilizing bacteria (PSB) in improving crop yield due to improved P levels in the soil ( Khourchi et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…The CND, CLREF, and CLRND methods had negative values for the net increase in production (Table 6), reflecting the inability to identify true cases of nutritional deficiency for B. Teixeira et al (2002) found Net d(Y) ranging from 20 to 70 t ha -1 in banana due to the correct diagnoses provided by CLREF for N and K. Silva et al (2020) evaluated the quality of the nutritional diagnosis of P by the CND method in sugarcane and reported negative values for Net d(Y). Morais et al (2019) verified that the CND method was the most suitable when compared with the CLCAL method to diagnose P in eucalyptus seedlings cultivated under a controlled environment using the Dickson quality index as a yield criterion to calculate Net d(Y).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the efficiency of nutritional diagnosis methods in soybean have only been indirectly conducted by comparing diagnoses produced by different methods (Urano et al, 2007;Kurihara et al, 2013) and without evaluating plant response to the nutritional assessment prognosis. Some authors have evaluated the performance of nutritional diagnosis for most crops based on plant response to correct the nutritional status (Beverly and Hallmark, 1992;Beverly, 1993;Morais et al, 2019;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the increased levels of toxic ions such as sodium and chlorine (Na + and Cl − ) negatively impact plant growth and yield by limiting water uptake and causing ion toxicity, which can lead to nutrient imbalances 6 . This has a significant effect on the root’s capacity to absorb water and results in stomatal closure altering CO 2 assimilation 7 and therefore photosynthesis efficiency 8 . Later, an imbalance of the photochemical phase takes place in chloroplasts, causing a series of secondary stresses including oxidative stress 9 , 10 where the continued exposure results in plant death 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, salt-stressed plants showed positive results after the optimisation of P nutrition in salt-affected soil 31 33 , 38 , 40 , 41 . Additionally, it is important to state that phosphorus absorption by plants differs depending on the physicochemical parameters of the soil 8 , the exudation and architecture of roots 42 , the method and frequency of P fertilizer application 43 , 44 , and the microbial rhizospheric activity 45 , 46 . In this regard, Kohler et al 47 found that the salt tolerance of lettuce plants was enhanced by Pseudomonas mendocina resulting in a decrease of catalase activity with an enhancement in the dry weight of leaves and proline concentration.…”
Section: Introductionmentioning
confidence: 99%